Energy deposition and formation of nanostructures in the interaction of highly charged xenon ions with gold nanolayers. (April 2023) - Stabrawa, I.; Banaś, D.; Kubala-Kukuś, A.; Jabłoński, Ł.; Jagodziński, P.; Sobota, D.; Szary, K.; Pajek, M.; Skrzypiec, K.; Mendyk, E.; Borysiewicz, M.; Majkić, M.D.; et al.
Abstract: The effect of the deposition of kinetic energy and neutralization energy of slow highly charged xenon ions on the process of the nanostructures creation at the surface of gold nanolayers is investigated. The nanolayers of thickness of 100 nm were prepared by e-beam evaporation of gold on crystalline silicon Si(100) substrate. The samples were irradiated at the Kielce EBIS facility of the Jan Kochanowski University (Kielce, Poland), under high vacuum conditions. The irradiations were performed for constant kinetic energy 280 keV and different ions charge states (Xe q+, q = 25, 30, 35, 36 and 40) and for constant charge state Xe 35+ and different kinetic energies: 280 keV, 360 keV, 420 keV and 480 keV. The fluence of the ions was on the level of 10 10 ions/cm 2 . Before and after irradiation the nanolayer surfaces were investigated using the atomic force microscope. As the result, well pronounced modifications of the nanolayer surfaces in the form of craters have been observed. A systematic analysis of the crater sizes (diameter on the surface and depth) allowed us to determine the influence of the deposited kinetic and the neutralization energy on the size of the obtained nanostructures. The results are theoretically interpreted within the micro-staircase model based on the quantum two-state vector model of the ionic Rydberg states population. The charge dependent ion–atom interaction potential inside the solid is used for the calculation of the nuclear stopping power. According to the model the formation of the nanostructures is governed by the processes of the ionic neutralization in front of the surface and the kinetic energy loss inside the solid. The interplay of these two types of processes in the surface structure creation is described by the critical velocity. Using the proposed theoretical model, the neutralization energy, deposited kinetic energy and critical velocities were calculated and compared qualitatively with the experimental results. The results are consistent (after normalization) with previous experimental data and molecular dynamics simulations for single ionized Xe and crystalline gold surface. Highlights: Interactions of slow xenon HCI with surface of gold nanolayers were investigated. Well pronounced modification of the surface in the form of craters were observed. Size of the craters depends on the neutralization energy and deposited kinetic energy. Within the micro-staircase model mechanism of the craters formation is proposed.